A catalyst for dehydrogenation of light hydrocarbons and its supporting process
By using a combined catalyst of tin and nickel metal and foamed alumina in the low-carbon hydrocarbon dehydrogenation process, the problem of insufficient catalyst binding force is solved, the selectivity of isobutene and the stability of the catalyst are improved, and efficient isobutene conversion is achieved.
Patent Information
- Application Number
- CN202411517541.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the low-carbon hydrocarbon dehydrogenation process, the catalyst-modified metal elements have weak binding force with the catalyst, resulting in easy loss in high-temperature catalytic reactions, reducing reaction selectivity and yield.
By dissolving SnCl2·2H2O in ethanol and reacting with the supported aluminum foam after ultrasonic treatment, a supported aluminum foam is formed, and calcined in a hydrogen atmosphere to fix nickel metal and tin metal to form an iron-nickel bimetallic organic framework and tin element Dispersed and vitrified with nickel elements on the foam alumina surface to enhance binding force.
The selectivity of isobutene and the life of the catalyst are improved, the loss of catalyst and carbon deposits are reduced, and the catalytic efficiency and the conversion of isobutene are improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of the process of preparing olefins by dehydrogenating light hydrocarbons, and specifically relates to a catalyst for dehydrogenating light hydrocarbons and a supporting process thereof. Background Art
[0002] With the growing demand for low-carbon olefins and the increasing utilization of abundant low-carbon hydrocarbon resources by the petrochemical industry, the catalytic dehydrogenation of isobutane to produce isobutylene, as the main product of low-carbon hydrocarbons, has become increasingly important. Isobutane dehydrogenation is a highly endothermic and equilibrium-limited reaction that requires relatively high temperatures and low pressures to obtain high isobutylene yields. However, higher reaction temperatures can lead to carbon deposition and catalyst deactivation, and also increase the occurrence of side reactions, thereby greatly reducing the selectivity of isobutylene.
[0003] The conversion rate and selectivity of isobutene can be improved by modifying the catalyst. The catalysts for isobutane dehydrogenation can be roughly divided into the following categories: the first category is precious metal catalysts; the second category is metal oxide catalysts; the third category is new non-metallic material catalysts; the first category of catalysts mainly refers to supported Pt metal or Ni metal catalysts, which are expensive and are mainly used in the Oleflex process and the STAR process. They are a dehydrogenation catalyst that can be used industrially; the second category of catalysts refers to certain transition metal elements in the form of oxides that act as the main components of the catalyst, including Cr, V, Ga, In, Zn, Fe, Mo and other metal elements.
[0004] In supported catalysts, one metal is usually loaded as the active ingredient of the catalyst. In order to improve the catalytic performance of the single metal catalyst, the conventional method is to introduce another one or more new metal elements as additives through the impregnation method on the basis of the single metal catalyst to modify the original catalyst.
[0005] Patent CN108499559A discloses a catalyst for isobutane dehydrogenation to isobutene, its preparation method and application. A platinum-based catalyst is used for catalysis. A carrier modified with attapulgite and a platinum metal active component are composited to form a catalyst containing a Pt-Mg bimetallic active component, thereby improving the activity of the catalyst in the isobutane dehydrogenation to isobutene reaction. However, the surface area of the carrier in this solution is low, and the binding force between the introduced metal and the catalyst is weak, which is easily lost in the high-temperature catalytic reaction, and the catalytic performance of the catalyst cannot be maintained, resulting in reduced selectivity of the catalyst and decreased yield. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that in the light hydrocarbon dehydrogenation process, the metal element modified by the catalyst has a weak bonding force with the catalyst, the metal element is easily lost in the high-temperature catalytic reaction, and the selectivity of the reaction is reduced, and to provide a catalyst for the dehydrogenation of light hydrocarbons and its supporting process.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A catalyst for dehydrogenation of light hydrocarbons, wherein the preparation method of the catalyst comprises the following steps:
[0009] SnCl2·2H2O is dissolved in ethanol and added dropwise to the loaded foam aluminum. After ultrasonic treatment for 40-60 minutes, the mixture is allowed to react for 3-4 hours, dried in a vacuum at 40-50°C for 2-3 hours, heated to 600-650°C in an air atmosphere, calcined for 2-3 hours, and then cooled to obtain loaded foam alumina. The mixture is then reacted in a hydrogen atmosphere at 600-650°C for 50-60 minutes, and finally cooled to room temperature in a N2 atmosphere to obtain a catalyst for dehydrogenation of light hydrocarbons.
[0010] Furthermore, the usage ratio of SnCl2·2H2O, ethanol and loaded foam aluminum is 0.6-1.2 g: 20-30 mL: 10-12 g.
[0011] Furthermore, the preparation method of the loaded aluminum foam is as follows:
[0012] The aluminum foam was immersed in 6M phosphoric acid solution under ultrasonic wave for 30-40min, washed with deionized water, and Ni(NO3)2·6H2O, FeSO4·7H2O and H2BDC were mixed and stirred in DMF in a reactor, and 0.4M NaOH solution was added dropwise, and the reaction was stirred for 20-30min. The aluminum foam was added, and the mixture was heated at 100-120°C for 8-10h. After cooling, the mixture was washed and dried to obtain loaded aluminum foam.
[0013] Further, the usage ratio of Ni(NO3)2·6H2O, FeSO4·7H2O, H2BDC, DMF, NaOH solution and aluminum foam is 2.6-3g: 0.8-1g: 2-2.2g: 120-150mL: 8-10mL: 10-12g.
[0014] Further, the preparation method of aluminum foam is as follows:
[0015] 10 wt % of polyethyleneimine anhydrous ethanol dispersion was dropped on Al-MOF and ground until the anhydrous ethanol was completely volatilized, and then heated to 400-450° C. in a nitrogen atmosphere for reaction for 20-30 minutes to obtain foamed aluminum.
[0016] Furthermore, the mass ratio of polyethyleneimine anhydrous ethanol dispersion to Al-MOF is 4-5:5-8.
[0017] Further, the Al-MOF preparation method is as follows:
[0018] In a reaction kettle, terephthalic acid and aluminum chloride are stirred and dissolved in a 40% by volume DMF aqueous solution, heated to 90-100° C. for reaction for 4-5 hours, cooled and vacuum filtered, washed with DMF and acetone in turn, and then vacuum dried to obtain Al-MOF.
[0019] Furthermore, the usage ratio of terephthalic acid, aluminum chloride and DMF aqueous solution is 30-40 g:30-40 g:2-3 L.
[0020] A supporting process for a catalyst for dehydrogenation of light hydrocarbons comprises the following steps:
[0021] The catalyst for dehydrogenation of light hydrocarbons is crushed and loaded into a fixed bed reactor. Quartz sand is laid on the upper and lower layers of the catalyst bed. The catalyst for dehydrogenation of light hydrocarbons is fixed on the lower layer and located in the constant temperature range of the tubular furnace. H2 is introduced into the fixed bed reactor and the temperature is raised to 550-600°C to activate the catalyst for dehydrogenation of light hydrocarbons for 1 hour. After purging with N2 for 30-40 minutes, the temperature is raised to 500-650°C, the pressure is 0.1-0.5Mpa, and the gas space velocity is 2000-5000h -1 , then introduce isobutane, hydrogen and water vapor, collect the dehydrogenation products, and complete the dehydrogenation of light hydrocarbons.
[0022] Furthermore, the feed gas volume ratio of isobutane, hydrogen and water vapor is 1:0.5-5:0.5-5.
[0023] Beneficial effects of the present invention:
[0024] The catalyst for dehydrogenation of low-carbon hydrocarbons prepared by the present invention improves the selectivity of isobutylene by introducing tin metal into a nickel-based catalyst, and vitrifies the metal organic framework by high temperature so that nickel metal and tin metal are dispersed and fixed on the surface of a foamed alumina carrier, so that the catalytic area is large, the metal bonding is firm, the catalyst life is long, and it is not easy to lose.
[0025] The present invention prepares nickel foam by using a nickel metal organic skeleton, and generates an iron-nickel bimetallic organic skeleton in situ on the surface of the nickel foam, so that the iron-nickel bimetallic organic skeleton is coated on the surface of the aluminum foam, and the molar ratio of nickel to iron is controlled so that the nickel metal content in the iron-nickel bimetallic organic skeleton is higher than that of the iron metal, so that the stannous ions can still retain most of the nickel metal when replacing the metal, and the tin element and the nickel element can better form an alloy at high temperature, so that the tin element modifies the nickel-based catalyst and improves the selectivity of isobutylene. At the same time, the iron oxide formed by the oxidation of the remaining iron element has alkalinity, can neutralize the acidic sites on the surface of the aluminum foam, reduce the coking and carbon deposition generated in the catalytic process, and improve the catalytic efficiency of the catalyst. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1: A catalyst for dehydrogenation of light hydrocarbons, the preparation method of which comprises the following steps:
[0028] Step 1. In a reactor, 30 g of terephthalic acid and 30 g of aluminum chloride were stirred and dissolved in 2 L of 40% DMF aqueous solution, heated to 90 ° C for reaction for 4 h, cooled and vacuum filtered, washed with DMF and acetone in turn, and then vacuum dried to obtain Al-MOF. 20 g of 10% polyethyleneimine anhydrous ethanol dispersion was dropped on 25 g of Al-MOF and ground. After grinding until the anhydrous ethanol was completely volatilized, it was heated to 400 ° C in a nitrogen atmosphere for reaction for 20 min to obtain foamed aluminum.
[0029] Step 2: Soak the aluminum foam in 6M phosphoric acid solution under ultrasound for 30 minutes. After washing with deionized water, mix 2.6g Ni(NO3)2·6H2O, 0.8g FeSO4•7H2O and 2g H2BDC in 120mL DMF in a reactor, add 8mL 0.4M NaOH solution, stir and react for 20 minutes, add 10g aluminum foam, heat at 100°C for 8h, wash with ethanol and deionized water after cooling, and dry at 70°C in air for 24h to obtain loaded aluminum foam.
[0030] Step 3: Dissolve 0.6 g SnCl2·2H2O in 20 mL ethanol, add dropwise to 10 g of loaded foam aluminum, ultrasonically treat for 40 min, let react for 3 h, vacuum dry at 40°C for 2 h, heat to 600°C at a rate of 5°C / min in an air atmosphere, calcine for 2 h, and cool to obtain loaded foam alumina, then react at a rate of 10°C / min in a hydrogen atmosphere at 600°C for 50 min, and finally cool to room temperature in a N2 atmosphere to obtain a catalyst for dehydrogenation of light hydrocarbons.
[0031] A supporting process for a catalyst for dehydrogenation of light hydrocarbons comprises the following steps:
[0032] The catalyst for dehydrogenation of light hydrocarbons was crushed and passed through a 60-mesh sieve and then loaded into a fixed-bed reactor. Quartz sand was laid on the upper and lower layers of the catalyst bed. The catalyst for dehydrogenation of light hydrocarbons was fixed on the lower layer and located in the constant temperature range of the tubular furnace. H2 was introduced into the fixed-bed reactor and the temperature was raised to 550°C to activate the catalyst for dehydrogenation of light hydrocarbons for 1 hour. After purging with N2 for 30 minutes, the temperature was raised to 500°C, the pressure was 0.1 MPa, and the gas space velocity was 2000 h -1 Then, isobutane raw gas, hydrogen and water vapor are introduced, the feed gas volume ratio of isobutane, hydrogen and water vapor is 1:0.5:0.5, and the dehydrogenation product is collected to complete the dehydrogenation of light hydrocarbons.
[0033] Embodiment 2: A catalyst for dehydrogenation of light hydrocarbons, comprising the following steps:
[0034] Step 1. In a reactor, 35 g of terephthalic acid and 35 g of aluminum chloride are stirred and dissolved in 2-3 L of 40% DMF aqueous solution, heated to 95°C for reaction for 4.5 h, cooled and vacuum filtered, washed with DMF and acetone in turn, and then vacuum dried to obtain Al-MOF, 22.5 g of 10% polyethyleneimine anhydrous ethanol dispersion is dropped on 30 g of Al-MOF and ground, and after grinding until the anhydrous ethanol is completely volatilized, heated to 425°C in a nitrogen atmosphere for reaction for 25 min to obtain foamed aluminum.
[0035] Step 2: Soak the aluminum foam in 6M phosphoric acid solution under ultrasound for 35 minutes. After washing with deionized water, mix 2.8g Ni(NO3)2·6H2O, 0.9g FeSO4·7H2O and 2.1g H2BDC in 135mL DMF in a reactor, add 9mL 0.4M NaOH solution, stir and react for 25 minutes, add 11g aluminum foam, heat at 110°C for 9h, wash with ethanol and deionized water after cooling, and dry at 72°C in air for 27h to obtain loaded aluminum foam.
[0036] Step 3: Dissolve 0.9 g SnCl2·2H2O in 25 mL ethanol, add dropwise to 11 g loaded foam aluminum, ultrasonically treat for 50 min, let stand to react for 3.5 h, vacuum dry at 45 ° C for 2.5 h, then heat to 625 ° C at a rate of 5 ° C / min in an air atmosphere, calcine for 2.5 h, and then cool to obtain loaded foam alumina, then react at a rate of 10 ° C / min in a hydrogen atmosphere at 625 ° C for 55 min, and finally cool to room temperature in a N2 atmosphere to obtain a catalyst for dehydrogenation of light hydrocarbons.
[0037] A supporting process for a catalyst for dehydrogenation of light hydrocarbons comprises the following steps:
[0038] The catalyst for dehydrogenation of light hydrocarbons was crushed and passed through a 70-mesh sieve and then loaded into a fixed-bed reactor. Quartz sand was laid on the upper and lower layers of the catalyst bed. The catalyst for dehydrogenation of light hydrocarbons was fixed on the lower layer and located in the constant temperature range of the tubular furnace. H2 was introduced into the fixed-bed reactor and the temperature was raised to 575°C to activate the catalyst for dehydrogenation of light hydrocarbons for 1 hour. After purging with N2 for 35 minutes, the temperature was raised to 600°C, the pressure was 0.3 MPa, and the gas space velocity was 3500 h -1 Then, isobutane raw gas, hydrogen and water vapor are introduced, the feed gas volume ratio of isobutane, hydrogen and water vapor is 1:3:3, and the dehydrogenation product is collected to complete the dehydrogenation of light hydrocarbons.
[0039] Embodiment 3: A catalyst for dehydrogenation of light hydrocarbons, comprising the following steps:
[0040] Step 1. In a reactor, 40 g of terephthalic acid and 40 g of aluminum chloride were stirred and dissolved in 3 L of 40% DMF aqueous solution, heated to 100 ° C for reaction for 5 h, cooled and vacuum filtered, washed with DMF and acetone in turn, and then vacuum dried to obtain Al-MOF. 25 g of 10% polyethyleneimine anhydrous ethanol dispersion was dropped on 40 g of Al-MOF and ground. After grinding until the anhydrous ethanol was completely volatilized, it was heated to 450 ° C in a nitrogen atmosphere for reaction for 30 min to obtain foamed aluminum.
[0041] PEI begins to decompose at 160°C and completely decomposes at 370°C. The decomposition temperature is lower than the melting point of Al-MOF. The carbon dioxide, ammonia and hydrogen produced by the decomposition will increase the volume of Al-MOF and form foamed aluminum.
[0042] Step 2: Soak the aluminum foam in 6M phosphoric acid solution under ultrasound for 40 minutes. After washing with deionized water, mix 3g Ni(NO3)2·6H2O, 1g FeSO4•7H2O and 2.2g H2BDC in 150mL DMF in a reactor, add 10mL 0.4M NaOH solution, stir and react for 30 minutes, add 12g aluminum foam, heat at 120°C for 10h, wash with ethanol and deionized water after cooling, and dry at 75°C in air for 30h to obtain loaded aluminum foam.
[0043] The alumina foam is ultrasonically treated in phosphoric acid to remove impurities and oxide layer on the surface of the alumina foam, and micro-pits are corroded on the surface of the alumina foam to further increase the surface area of the alumina foam. Then, an iron-nickel bimetallic MOF is in situ generated on the surface of the alumina foam by a hydrothermal reaction to load iron and nickel into the alumina foam.
[0044] Step 3: Dissolve 1.2 g SnCl2·2H2O in 30 mL ethanol, add dropwise to 12 g loaded foam aluminum, ultrasonically treat for 60 min, let react for 4 h, dry at 50°C for 3 h, heat to 650°C at a rate of 5°C / min in an air atmosphere, calcine for 3 h, and cool to obtain loaded foam alumina, then react at a rate of 10°C / min in a hydrogen atmosphere at 650°C for 60 min, and finally cool to room temperature in a N2 atmosphere to obtain a catalyst for dehydrogenation of light hydrocarbons.
[0045] Stannous ions are dispersed on the surface of the loaded aluminum foam by an impregnation method. Stannous ions undergo a replacement reaction with some iron atoms and nickel atoms in the iron-nickel bimetallic MOF loaded on the surface of the aluminum foam, and the stannous ions are dispersed on the surface of the bimetallic MOF. After high-temperature oxidation-reduction, the aluminum foam is oxidized into aluminum oxide, and the iron-nickel bimetallic MOF is vitrified and attached to the surface of the aluminum oxide. The tin element on the surface of the iron-nickel bimetallic MOF is reduced to tin metal and composited with the iron-nickel bimetallic MOF to form a nickel-tin-iron composite catalyst with the aluminum foam as the carrier. When the tin metal is introduced into the nickel-tin-iron composite catalyst, The interaction between isobutylene and the catalyst surface is reduced, the occurrence of secondary reactions is reduced, and the selectivity of isobutylene is improved. The iron oxide formed by the oxidation of iron is alkaline, which can neutralize the acidic sites on the surface of foamed alumina, reduce coking and carbon deposition, and improve the catalytic efficiency of the catalyst. The interaction between nickel and tin in the nickel-tin composite catalyst is enhanced, and the fixing effect produced by the vitrification of the bimetallic MOF fixes tin, iron and nickel on the catalyst surface, reducing the loss of tin, iron and nickel. The catalyst has a long service life, high catalytic efficiency and high selectivity for isobutylene.
[0046] A supporting process for a catalyst for dehydrogenation of light hydrocarbons comprises the following steps:
[0047] The catalyst for dehydrogenation of light hydrocarbons was crushed and passed through an 80-mesh sieve and then loaded into a fixed-bed reactor. Quartz sand was laid on the upper and lower layers of the catalyst bed. The catalyst for dehydrogenation of light hydrocarbons was fixed on the lower layer and located in the constant temperature range of the tubular furnace. H2 was introduced into the fixed-bed reactor and the temperature was raised to 600°C to activate the catalyst for dehydrogenation of light hydrocarbons for 1 hour. After purging with N2 for 40 minutes, the temperature was raised to 650°C, the pressure was 1 MPa, and the gas space velocity was 5000 h-1. -1 Then, isobutane raw gas, hydrogen and water vapor are introduced, the feed gas volume ratio of isobutane, hydrogen and water vapor is 1:5:5, and the dehydrogenation product is collected to complete the dehydrogenation of light hydrocarbons.
[0048] Comparative Example 1: The difference from Example 1 is that aluminum oxide powder is used instead of foamed aluminum.
[0049] Comparative Example 2: The difference from Example 1 is that in step 2, FeSO4•7H2O is not added.
[0050] Comparative Example 3: The difference from Example 1 is that nickel and tin are loaded on the surface of foamed alumina by an impregnation method, and the steps are as follows:
[0051] Ni(NO3)2·6H2O and SnCl2·2H2O were dissolved in ethanol, added dropwise to aluminum foam, subjected to ultrasonic treatment for 1 h, dried at 70-80°C for 2-3 h, heated to 600-650°C at a rate of 5°C / min in an air atmosphere, calcined for 2-3 h, and then cooled to obtain a catalyst for dehydrogenation of light hydrocarbons.
[0052] The reagents in the examples and comparative examples were purchased from conventional commercial sources.
[0053] The catalysts for dehydrogenation of light hydrocarbons prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for isobutane dehydrogenation performance. The catalyst for dehydrogenation of light hydrocarbons weighed 1 g and was placed in a quartz tube reactor with an inner diameter of 8.0 mm and a length of 40 cm. The catalyst for dehydrogenation of light hydrocarbons was activated at 600° C. for 1 h in a hydrogen atmosphere. After purging the hydrogen in the reactor with nitrogen, the pressure was set to 1 MPa, the reaction temperature was 600° C., and the space velocity was 4000 h / min. -1 The feed volume ratio of isobutane, hydrogen and water vapor was 1:3:3, the reaction time was 20 hours, and the isobutylene content and isobutane content in the product were measured.
[0054] The calculation method of isobutane conversion rate and isobutene selectivity is as follows: isobutane conversion rate = (isobutane content in feedstock - isobutane content in product) / isobutane content in feedstock × 100wt%, isobutene selectivity = (isobutene content in product - isobutene content in feedstock) / (isobutane content in feedstock - isobutane content in product) × 100wt%; the results are shown in Table 1:
[0055] Table 1
[0056] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Conversion rate wt% 53.2 53.6 53.9 42.8 48.3 49.7 Selectivity wt% 98.1 98.4 98.5 91.3 96.7 97.2
[0057] The catalyst for dehydrogenation of light hydrocarbons was regenerated by charcoal burning at 400°C and then tested for isobutane dehydrogenation performance. The results are shown in Table 2:
[0058] Table 2
[0059] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Conversion rate wt% 52.4 52.7 53.1 40.3 47.2 45.8 Selectivity wt% 97.4 97.6 97.9 90.2 96.1 90.6
[0060] It can be seen from Table 1 and Table 2 that the catalysts for dehydrogenation of light hydrocarbons prepared in Examples 1 to 3 of the present invention have high selectivity for isobutylene, reaching more than 98%, and high conversion rate for isobutylene, reaching more than 53%. After charcoal burning and regeneration, the conversion rate of Examples 1 to 3 is only slightly reduced, indicating that the tin element in the catalyst for dehydrogenation of light hydrocarbons prepared in the present invention has a strong binding force with the nickel-based catalyst, is not easy to fall off, and can stably maintain the catalytic activity and high selectivity for isobutylene.
[0061] In Comparative Example 1, since alumina powder is used instead of foamed aluminum, the surface area of the catalyst is small, the catalytic activity is low, the binding force and dispersibility with the nickel-iron bimetallic organic framework are poor, and therefore the conversion rate and selectivity are low; in Comparative Example 2, since it does not contain iron, the generated catalyst has no neutralizing effect on the acidic sites on the surface of the foamed aluminum oxide, carbon deposition is serious, and carbon deposition is still easy to occur after charcoal burning regeneration, so the conversion rate and selectivity are low; in Comparative Example 3, since the tin-nickel alloy is deposited on the surface of the foamed aluminum oxide by the impregnation method, the binding force of the tin-nickel alloy with the carrier foamed aluminum oxide is poor, the dispersibility is low, and the loss of tin and nickel elements after charcoal burning regeneration is large, and the conversion rate and selectivity are significantly reduced.
[0062] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A catalyst for dehydrogenation of light hydrocarbons, characterized in that: The preparation method of the catalyst comprises the following steps: SnCl2·2H2O is dissolved in ethanol, and then added dropwise to the loaded foam aluminum. After ultrasonic treatment for 40-60 minutes, the mixture is allowed to react for 3-4 hours, and then vacuum dried at 40-50°C for 2-3 hours. The mixture is then heated to 600-650°C in an air atmosphere, calcined for 2-3 hours, and then cooled to obtain loaded foam aluminum oxide. The mixture is then reacted in a hydrogen atmosphere at 600-650°C for 50-60 minutes, and finally cooled to room temperature in a N2 atmosphere to obtain a catalyst for dehydrogenation of light hydrocarbons. The preparation method of the loaded aluminum foam is as follows: The aluminum foam is immersed in a 6M phosphoric acid solution under ultrasonic wave for 30-40 minutes, washed with deionized water, and Ni(NO3)2·6H2O, FeSO4·7H2O and H2BDC are mixed and stirred in DMF in a reaction kettle, and a 0.4M NaOH solution is added dropwise, and the reaction is stirred for 20-30 minutes, and the aluminum foam is added, and the mixture is heated at 100-120°C for 8-10 hours, and washed and dried after cooling to obtain the loaded aluminum foam; The preparation method of the aluminum foam is as follows: Dropping 10 wt% of polyethyleneimine anhydrous ethanol dispersion on Al-MOF and grinding until the anhydrous ethanol is completely volatilized, heating to 400-450° C. in a nitrogen atmosphere and reacting for 20-30 min to obtain foamed aluminum; The Al-MOF preparation method is as follows: In a reaction kettle, terephthalic acid and aluminum chloride are stirred and dissolved in a 40% by volume DMF aqueous solution, heated to 90-100° C. for reaction for 4-5 hours, cooled and vacuum filtered, washed with DMF and acetone in turn, and then vacuum dried to obtain Al-MOF.
2. A catalyst for dehydrogenation of light hydrocarbons according to claim 1, characterized in that: The usage ratio of SnCl2·2H2O, ethanol and loaded foam aluminum is 0.6-1.2g:20-30mL:10-12g.
3. A catalyst for dehydrogenation of light hydrocarbons according to claim 1, characterized in that: The dosage ratio of Ni(NO3)2·6H2O, FeSO4·7H2O, H2BDC, DMF, NaOH solution and foamed aluminum is 2.6-3g: 0.8-1g: 2-2.2g: 120-150mL: 8-10mL: 10-12g.
4. A catalyst for dehydrogenation of light hydrocarbons according to claim 1, characterized in that: The mass ratio of the polyethyleneimine anhydrous ethanol dispersion to the Al-MOF is 4-5:5-8.
5. The catalyst for dehydrogenation of light hydrocarbons according to claim 1, characterized in that: The usage ratio of terephthalic acid, aluminum chloride and DMF aqueous solution is 30-40g:30-40g:2-3L.
6. The use of a catalyst for dehydrogenation of light hydrocarbons according to claim 1, characterized in that: The application comprises the following steps: The catalyst for dehydrogenation of light hydrocarbons is crushed and loaded into a fixed bed reactor. Quartz sand is laid on the upper and lower layers of the catalyst bed. The catalyst for dehydrogenation of light hydrocarbons is fixed on the lower layer and located in the constant temperature range of the tubular furnace. H2 is introduced into the fixed bed reactor and the temperature is raised to 550-600°C to activate the catalyst for dehydrogenation of light hydrocarbons for 1 hour. After purging with N2 for 30-40 minutes, the temperature is raised to 500-650°C, the pressure is 0.1-0.5Mpa, and the gas space velocity is 2000-5000h -1 , then introduce isobutane, hydrogen and water vapor, collect the dehydrogenation products, and complete the dehydrogenation of light hydrocarbons.
7. Use of a catalyst for dehydrogenation of light hydrocarbons according to claim 6, characterized in that: The feed gas volume ratio of isobutane, hydrogen and water vapor is 1:0.5-5:0.5-5.